Identification of Serum Biomarkers for Differentiating Epileptic Seizures from Psychogenic Attacks Using a Proteomic Approach; a Comparative study - Parvareshi Hamrah, Mohsen; Rezaei Tavirani, Mostafa; Movahedi, Monireh; Ahmadi Karvigh, Sanaz (Archives of Academic Emergency Medicine, 2020)
Introduction: Differentiating actual epileptic seizures (ESs) from psychogenic non-epileptic seizures (PNES) is of great interest. This study compares the serum proteomics of patients diagnosed with ESs and PNES. Methods: Eight patients with seizure (4 with PNES and 4 with TLE (temporal lope epilepsy)) were enrolled in this comparative study. Venous blood samples were drawn during the first hour following the seizure. Standard protein purification technique was employed and proteins were subsequently separated via 2-D electrophoresis. After comparison of the serum proteomes from the two groups, protein expression was analyzed. The differentially expressed bands were determined using both matrix-assisted laser ionization time-of-flight (MALDI/TOF) and electrospray ionization quadruple mass spectrometry (MS). Results: This study identified 361 proteins, the expression of 110 proteins increased, and 87 proteins decreased in the PNES group compared with TLE group. Four separate proteins were finally identified with MALDI/TOF MS analysis. Compared with PNES group, alpha 1-acid glycoprotein, ceruloplasmin, and S100-β were down-regulated and malate dehydrogenase 2 was up-regulated in the serum of TLE patients. Conclusion: Our results indicated that changes in serum levels of S100-β, ceruloplasmin, alpha 1-acid glycoprotein 1, and after seizure could be introduced as potential markers to differentiate ES from PNES; however, more advanced studies are required to reach a better understanding of the underlying mechanisms.